Combined approach for management of gynecomastia: Subcutaneous mastectomy and liposuction - Bajracharya, Amir (Journal of Kathmandu Medical College, 2018)
Introduction: There are different modalities for the treatment of gynecomastia. Open surgical techniques have become less popular with the advent of liposuction and its variants, including power-assisted and ultrasound-assisted liposuction.Methodology: This is a descriptive study done to observe the combined approach of liposuction and subcutaneous mastectomy for the treatment of gynecomastia and to evaluate aesthetic aspects using Surgeon’s evaluation score for size, shape, scarring, overall outcome and patient satisfaction score by using visual analogue scale. Inclusion criteria consist of all the patients with bilateral or unilateral gynecomastia using Simon Grade I and II. , Exclusion criteria consist of patients having pseudogynecomastia, pathological and with Simon Grade III gynecomastia. Frequency analysis was done using Statistical Package for Social Sciences version 20.0.Results: Twenty-one patients were included in the study, out of which there were 12 (57%) cases of bilateral, six (29%) cases of right and three (14%) cases of left sided gynecomastia. Mean age was 23.8 years range (14-32) years, mean body mass index 22.52 kg/m2 (18-26) kg/m2 mean volume of fat removal through liposuction 136.43 ml (40-300) ml, and mean resected breast tissue was 89.29 gm (40-150) gm. In our study 33.3% cases were of Simon Grade I and 66.7 % cases were of Grade II gynecomastia with one (4.7%) case had post-operative hematoma. With combined approach liposuction and subcutaneous mastectomy results showed overall excellent patient satisfaction, minimal complication, less scarring and cost effective.Conclusions: Management of gynecomastia with subcutaneous mastectomy and liposuction can be a combined approach with less complication and overall excellent patient satisfaction.